2003
DOI: 10.1093/treephys/23.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous gibberellin and auxin on shoot elongation and vegetative bud development in seedlings of Pinus sylvestris and Picea glauca

Abstract: The hormonal control of stem unit (foliar appendage and axillary structure, if present, plus subtending internode) number and length was investigated in shoots of Scots pine (Pinus sylvestris L.) and white spruce (Picea glauca (Moench) Voss). Seedlings were treated with six gibberellins (GA1, GA3, GA4, GA5, GA9 and GA20) and two auxins (indole-3-acetic acid (IAA) and naphthaleneacetic acid (NAA)) when either neoformed growth was occurring or the terminal vegetative bud was developing. Hormones were applied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 37 publications
2
20
0
1
Order By: Relevance
“…Gibberellins form a large family of tetracyclic diterpenoids and play important roles in modulation of seed plant growth and development (Little and MacDonald 2003; Waghorn et al 2003). GA was first isolated from Gibberella fujikuroi in the 1930s (Takahashi et al 1991).…”
Section: Evolutionarily Conserved Ga‐gid1‐della Growth‐regulatory Mecmentioning
confidence: 99%
“…Gibberellins form a large family of tetracyclic diterpenoids and play important roles in modulation of seed plant growth and development (Little and MacDonald 2003; Waghorn et al 2003). GA was first isolated from Gibberella fujikuroi in the 1930s (Takahashi et al 1991).…”
Section: Evolutionarily Conserved Ga‐gid1‐della Growth‐regulatory Mecmentioning
confidence: 99%
“…Hence, BA alone and combined with IBA had similar effects on elongation. It is well documented that auxins, gibberellins and polyamines usually favor shoot elongation (Little and MacDonald, 2003;Nuri, 2004), while cytokinins may act in a different manner and favor shoot sprouting (Perez-Tronero et al, 2000). However, the effects of these classes of plant growth regulator are not always the same and depend on variables such as the plant species, the type and the concentrations of the growth regulators, and growth conditions.…”
Section: Ba + Iba Combinations Resulted In Higher Multiplication Of Amentioning
confidence: 99%
“…[13] and Dalbergia odorifera T. Chen [14]; Foliar application of GA 3 could increase height growth, photosynthetic pigment contents of Pogostemon cablin Benth. [15]; Little and Macdonald's [16] study showed that gibberellins (GA 1 , GA 3 and GA 4 ) could accelerate shoot elongation and vegetative bud development of Pinus sylvestris L. and Picea glauca (Moench) Voss seedlings. These findings and experiences will be contributed for regulating seedling growth by combined application of PBZ and gibberellins although there is no case study using comprehensively both regulators.…”
Section: Introductionmentioning
confidence: 99%